2021
DOI: 10.1590/1806-908820210000041
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Quantification, and Ftir Characterization of Bark Tannins of Four Forest Species Grown in Northeast Brazil

Abstract: Condensed tannins are chemical compounds derived from the secondary metabolism of plants. They are of particular interest due to their broad range of technological uses and applications. The objective of this study was to extract, quantify, and characterize by Fourier-transform infrared spectroscopy (FTIR) the bark tannins of four forest species grown in Northeast Brazil: Acacia mangium, Azadirachta indica, Mimosa tenuiflora, and Mimosa caesalpiniifolia. Bark samples were collected from 5 trees of each species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…There was no statistical diff erence between the experimental treatments T1 and T2 for TSC and CTC (Table 6). Assessing the TSC in M. caesalpiniifolia bark from 5-year-old trees, Marques et al (2021) determined a value for TSC of 9.18%, close to the values found here for T1 and T2 of 8.57 and 7.12% respectively. TSC corresponds to the hotwater-soluble extractives from the bark, while CTC indicates the content of extractable tannins in each material.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…There was no statistical diff erence between the experimental treatments T1 and T2 for TSC and CTC (Table 6). Assessing the TSC in M. caesalpiniifolia bark from 5-year-old trees, Marques et al (2021) determined a value for TSC of 9.18%, close to the values found here for T1 and T2 of 8.57 and 7.12% respectively. TSC corresponds to the hotwater-soluble extractives from the bark, while CTC indicates the content of extractable tannins in each material.…”
Section: Methodssupporting
confidence: 83%
“…We found a statistical diff erence between the experimental treatments T1 and T2, with the highest value found for the extracts from the bark of the non-thinned plot (T2), 73.31%. However, this value is lower than that of Marques et al (2021), 91.27%. When subjected to stressful situations, plants show alteration in the production of secondary metabolites as a defense mechanism (Isah, 2019).…”
Section: Methodscontrasting
confidence: 57%
See 1 more Smart Citation
“…The presence of peaks between 1200 cm −1 and 1350 cm −1 indicates that phenolic and anthocyanic compounds are contained in the samples. This was clearly pointed out by Marques [41].…”
Section: Fourier-transformation-infrared Spectroscopy (Ft-ir) Of the ...mentioning
confidence: 79%
“…3 , Table 4 ). In previous studies, FT-IR analysis revealed that the alkaloids exhibited NH stretching, phenols and flavonoids had OH stretching (Devi and Battu, 2019 ), saponins had C=O stretching (Bajad and Pardeshi, 2016 ), tannins possess C=C stretching (Marques, 2021 ). The outcomes of the current study revealed that dichloromethane and ethyl acetate extracts of L. aspera have alkaloids, flavonoids, phenols, saponins, and tannins, whereas the hexane extract of L. aspera showed the presence of alkaloids and tannins and these are in correlation with previous studies of Das et al ( 2011 ), Vasudha et al ( 2019 ).…”
Section: Resultsmentioning
confidence: 97%